Symbolism in Film Turning Red: Representation of Chinese Culture Through Animated Movies - Lambok Hermanto Sihombing; Resty Nadia Al’ula (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
Disney and Pixar film has unique stories and visuals that focus on a mother and daughter relationship as they deal with the big changes of their adolescence. Film is a work of art that depicts life in the universe in such a way that those who watch it gain a broad understanding. Turning Red is one of Disney Hotstar's most popular animated films. This film depicts the Buddhist aspects of religion, customs, and daily living with many significant qualities. This study aims to investigate the Chinese symbols represented in the film Turning Red. To support the analysis, the authors used a qualitative methodology to apply the Mise en Scene approach of Manon de Reeper, the Symbolism concept of Charles Sanders Pierce, and the Representation theory of Stuart Hall. The results indicate that the film Turning Red attempts to represent Chinese cultural identity through symbols such as food, architecture, and animals.